ELABORAREA ȘI STUDIUL AEROMATERIALULUI ÎN BAZĂ DE TiO2 PENTRU APLICAȚII FOTOCATALITICE - Busuioc, Simon; Ciobanu, Vladimir; Braniște, Tudor; Zalamai, Victor; Ursachi, Veaceslav; Monaico, Eduard; Tighineanu, Ion (CEP USM, 2024)
We report on the fabrication process of TiO2 -based aeromaterial for environmental applica tions, such as wastewater treatment or as activated photocatalytic air filters. The TiO2 aeromate rial is obtained by Atomic Layer Deposition technique with the thickness of 50 nm on a substrate template consisting of ZnO microtetrapods, followed by the selective chemical etching of the ZnO template. The morphological and optical properties, chemical composition and crystalline quality of the fabricated aeromaterial are investigated. By implementing specific technological steps to enhance the crystalline quality of the TiO2 aeromaterial, it was possible to obtain materi als with either anatase phases or a mixed anatase-rutile phase.
FABRICATION AND INVESTIGATION OF TiO2 AEROMATERIAL FOR PHOTOCATALYTIC APPLICATIONS
BUSUIOC, Simon, CIOBANU, Vladimir, BRANIȘTE, Tudor, ZALAMAI, Victor, URSACHI, Veaceslav, MONAICO, Eduard, TIGHINEANU, Ion. Elaborarea și studiul aeromaterialului în bază de TiO2 pentru aplicații fotocatalitice. In: Integrare prin cercetare și inovare: conferința științifică națională cu participare internațională. Ştiinţe ale naturii și exacte, 9-10 noiembrie 2023. CEP USM, 2024, pp. 726-731. ISBN 978-9975-62-690-3.
Keywords: titanium dioxide; aeromaterial; ZnO microtetrapods; photocatalysis; sacrificial template